Einige extremale Aufgaben für die Klassen Kn(E) und P(E) - Kirjatsky, E. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. Кирьяцкий. Некоторые экстремальные задачи в классах Kn(E) и Р(Е) E. G. Kirjackis. Kai kurie ekstremaliniai uždaviniai Kn(E) ir P(E) klasėse